2013
DOI: 10.1159/000345898
|View full text |Cite
|
Sign up to set email alerts
|

Fine Needle Aspiration Cytology: A Tool to Diagnose Cervical and Vaginal Endometriosis in Low-Income Places

Abstract: Regarded as infrequent, vaginal and cervical endometriosis is probably more common than is generally realized. The apparent rarity of the lesion may be ascribed to the limited awareness of its clinical appearance, combined with technical difficulty in obtaining suitable biopsy material for confirmation. Thus, clinical recognition and tissue confirmation become essential. This paper focuses on vaginal and cervical endometriosis, documenting the clinical, macroscopic, cytological and colposcopic findings in 4 ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Peritoneal washing is a method routinely used in oncology pelvic surgery and has been recommended in patients with suspected pelvic endometriosis. Peritoneal endometriosis can be challenging to diagnose due to paucicelullarity 2 differently from fine‐needle aspiration of extrapelvic endometriosis, which previous studies demonstrated good accuracy 5,6 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Peritoneal washing is a method routinely used in oncology pelvic surgery and has been recommended in patients with suspected pelvic endometriosis. Peritoneal endometriosis can be challenging to diagnose due to paucicelullarity 2 differently from fine‐needle aspiration of extrapelvic endometriosis, which previous studies demonstrated good accuracy 5,6 …”
Section: Introductionmentioning
confidence: 99%
“…Peritoneal endometriosis can be challenging to diagnose due to paucicelullarity 2 differently from fine-needle aspiration of extrapelvic endometriosis, which previous studies demonstrated good accuracy. 5,6 On cytology, the presence of at least two of the following elements on a centrifuged peritoneal fluid is sufficient for the diagnosis of pelvic endometriosis: endometrial epithelial cells (3d clusters, tubular structures, and single epithelial cells), stromal cells (syncytial clusters of spindle cells with small nuclei), and hemosiderin-laden macrophages. 7 We aimed to assess the sensitivity, specificity, and predictive values of cytology of the fluid sediment in patients with pelvic endometriosis, diagnosed by laparoscopic-guided biopsy.…”
Section: Introductionmentioning
confidence: 99%